Effect of caffeine and vitamin C in structure and function of the thyroid gland male rats treatment by dimethoate - Hussein Khudair AL- Mayali; Ali Abd-Alameer Al-anbaki (Al-Qadisiyah Journal of Pure Science, 2017)
Conducted the current study to determine the positive effects of caffeine and vitamin C in reducing the toxicity of pesticide dimethoate , as used (50) male mature, divided the animals into two groups subdivided included each group of 25 animals and these were divided into five groups secondary included each group 5 animals. Control group dealt with drinking water usual , The first treatment: given pesticide dimethoate concentration of 30 mg / kg of body weight, treatment II: given pesticide dimethoate concentration of 30 mg / kg and caffeine concentration of 20 mg / kg of body weight, treatment III: given vitamin C concentration 100 mg / kg of body weight , treatment IIII: dimthoate pesticide concentration 30 mg / kg and caffeine concentration of 20 mg / kg of body weight and vitamin C concentration of 100 mg / kg of body weight. and after 3 and 6 weeks and weighed the animals and took blood for the purpose of evaluating measure the levels of hormones, thyroid (T4, T3) and TSH , , and catalse and glutathione. I explained to animals and eradicated the thyroid gland and to conduct histological study . the analysis showed statistically significant decrease (P <0.05) levels of hormones, thyroid (T4, T3) and high moral (P <0.05) in the level of TSH for a pesticide compared with control as well as with the rest of the aggregates treatment , and saw results a significant decrease (P <0.05) in the level of antioxidants catalse and glutathion in the group treated first pesticide dimethoate compared with the control , as well as with the rest of aggregates treatment, either study textile has recorded a significant decrease (P <0.05) in diameters follicles and size colloid compared with the control , as well as with the rest of the treatment groups .It follows from the results of the study , exposure to dimethoate led to the events of changes in the standards biochemical blood rats treated pesticide although the intensity changes are all grown up duration of exposure , and the study proved that giving caffeine and vitamin C together or separately synchronously his role is effective in reducing the damage and toxic effects caused by dimethoate in the effectiveness and installation of the thyroid gland in addition to biochemical parameters .